AN ASSESSMENT OF ENVIRONMENTAL NOISE POLLUTION OF JODHPUR, RAJASTHAN, INDIA - Saraswat, Punit (MATTER: International Journal of Science and Technology, 2018)
Jodhpur is the second largest city of Rajasthan, India. In recent years Jodhpur have expanded exponentially with increase in population, industries, vehicles etc. and this growth has created the problems like noise, air and waste pollution to name a few. Noise pollution is one of the problems which are not being addressed seriously and hence the present study was undertaken. The noise levels Leq dB (A) were monitored at three sites namely Shastri Nagar (Lachoo memorial College of Science and Technology-LMC), Basni Phase I, and AIIMS main gate road site, grouped as Residential, Industrial and silence zone area respectively. The monthly observations were recorded during morning hour (8-10AM), noon hours (12-2PM), and evening hour (5-7 PM) using sound level meter (Envirotech Instruments) model SLM 100, taking the readings at an interval of 1min, from December 2017 to April 2018. The maximum noise level recorded at Shastri Nagar,(LMC) site was 87.0dB in January 2018 (12-2PM), at Basni Phase I site was 97.2dB in December 2017 (8-10 AM), and was recorded 91.6dB in April 2018 (5-7 PM) at AIIMS main gate road site. The average noise level were found to be more than prescribed limits set by Central Pollution control Board (CPCB 2000) at all the three sites for all the five months and all the three recording hours (8-10AM, 12-2PM, and 5-7 PM), except at Basni Phase I site when it was observed to be slightly below (CPCB limit 75 dB - observed level 71.66 dB &73.67 dB ) in January 2018(8-10 AM) and February 2018 (12-2 PM) respectively. The present study can be fruitful in devising effective methods to curb this problem.